BMS Control of UPS for Hybrid Energy System using IoT - G., Arul Mozhi; P., Achchaya; S., Praveen Kumar; M., Surendhar; B., Sathyaseelan (Journal of Electronics and Informatics, 2025)
This study explores the integration of renewable energy sources, namely wind and solar power, into a home power backup system. In the event of a main power outage, an uninterruptible power supply (UPS) automatically activates to provide electricity to the household. As the UPS operates, its battery gradually depletes. When the battery reaches a low charge threshold, the system initiates charging through renewable energy sources. Once the battery is fully recharged, any surplus energy is redirected to the electrical grid. The system incorporates IoT (Internet of Things) technology using an ESP32 microcontroller to monitor and display real-time data on the battery’s State of Charge (SOC) and State of Health (SOH), enabling users to track system performance and anticipate maintenance requirements.